Ülevaade Eesti ohvitseride andmekogu allikatest [An overview of sources for the database of Estonian officers] - Kraft, Ülle (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
The database of Estonian officers in 1918–1940 was founded in 2007 and it has become very popular among those interested in military history.The database includes data on about 10,000 officers, doctors and military clerks while its compilation is still in progress. Information is gathered from various sources as the key sources are lists. People find their names on various lists during their lifetime – class list, list of university graduates, list of conscripts/mobilized etc. Unfortunately, Estonian officers were more likely to feature on lists of people arrested by the Soviet security agencies or even on lists of those who have fallen, died in prison camps or been executed. (Longer version of the current abstract is included in the article, starting from p 311.)